(untitled) (Research, Society and Development, 2022)
Breast cancer is a disease caused by the uncontrolled multiplication of abnormal cells in the breast, which forms a tumor with the potential to invade other organs. There are several types of breast cancer. Some grow quickly, while others grow slowly. Most cases, when treated properly and in a timely manner, have a good prognosis. The most used diagnostic methods for breast cancer are breast self-examination, clinical breast examination and mammography. Knowing how to use them properly, favoring women’s access to these methods and, if necessary, subsequent to immediate treatment, should be a fundamental strategy for early diagnosis. The treatment of breast cancer depends on the stage of the disease (stage) and the type of tumor. It may include surgery, radiation therapy, chemotherapy, hormone therapy, and biological therapy (targeted therapy). When the disease is diagnosed early, treatment has the greatest curative potential. Therefore, this study was an integrative review with the objective of analyzing methods of diagnosis and treatment in all stages of breast cancer. The study included the choice of 19 articles, found in several more recent electronic databases, which contributed to the conclusion of the study.